The use of big data and algorithms on digital advertising - De San Martin, Gülşah Zamorano (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: With the impact of digital transformation, big data and algorithms have had a significant impact on digital advertising. Rather than the visual or content richness of advertisements, this transition means organizations refining their business strategy, getting to know their clients better, and delivering relevant goods and services. In digital advertising, Turkey's advertising corporations gain from big data and algorithms. The role of big data and algorithms in digital advertising was attempted to be established in this qualitative research study, which involved 23 (16 male, 7 female) persons from relevant firms. The participants were provided with the semi-structured interview form prepared in this regard, and their thoughts on the usage of big data and algorithms were gathered. The themes were revealed when the data obtained for the study was examined using the content analysis approach in the Nvivo 12 program. Big data and algorithms are of great importance in digital advertising in this context; advertising companies should benefit from big data, based on the fact that almost everyone in the world provides data to big data, and the usefulness of big data and algorithms in ensuring correct product pricing are the situations stated by the participants. Participants explained their reasons for using big data and algorithms, the increase and change in customer demands (86.96 %), to be a pioneer in the competitive environment (78.26 %), evaluation of new market opportunities (73.91 %), development of new They are listed as goods and services (65.22%), current event and changes in the world (56.52%), and increase in stakeholder value (30.43%). Participants pointed out that personalization and accurate targeting (47.8%) for the advantages of big data and algorithms, direct access of advertisements to the targeted customer and contributing to the reduction of advertising expenditures (43.5%) are priority. Furthermore, the participants stated that the potential of big data and algorithms to access all consumer information violates ethical limits, which they believe is a negative. As a result, big data and algorithms are becoming increasingly important in the evolution of digital advertising in Turkey, and businesses are increasingly relying on them to stay competitive.

ÖZET: Dijital reklamcılık, dijital dönüşümün etkisiyle büyük veri ve algoritmalardan oldukça etkilenmiş durumda. Bu dönüşüm, sunulan reklamların görsel ya da içerik zenginliğinden öte, firmaların iş stratejilerini geliştirme, müşterilerini daha yakından tanıma ve buna uygun mal ve hizmet sunma anlamına gelmektedir. Türkiye’de reklam firmaları dijital reklamcılıkta büyük veri ve algoritmalardan faydalanmaktadır. Nitel araştırma yöntemiyle yürütülen bu çalışmada, ilgili firmalardan 23 (16 erkek, 7 kadın) kişiyle mülakat yapılmış ve dijital reklamcılıkta, büyük veri ve algoritmaların yeri saptanmaya çalışılmıştır. Bu kapsamda hazırlanan yapılandırılmış görüşme formu katılımcılara sunulmuş ve büyük veri ve algoritma kullanımına dair görüşleri öğrenilmiştir. Araştırma kapsamında toplanan veriler Nvivo 12 programında içerik analizi yöntemiyle analiz edilmiş ve temalar açığa çıkarılmıştır. Bu kapsamda büyük veri ve algoritmaların dijital reklamcılıkta büyük öneme sahip olduğu, dünyadaki neredeyse herkesin büyük veriye veri sağlamasına bağlı olarak, reklamcılık şirketlerinin büyük veriden faydalanmaları gerektiği, ürün fiyatlandırmalarının doğru olabilmesi için büyük veri ve algoritmaların kullanışlılığı, katılımcılar tarafından belirtilen durumlardır. Katılımcılar büyük veri ve algoritma kullanma nedenlerini; the increase and change in customer demands (86,96 %), to be a pioneer in the competitive environment (78,26 %), evaluation of new market opportunities (73.91 %), development of new goods and services (65,22 %), current event and changes in the world (56,52 %), and increase in stakeholder value (30,43 %) şeklinde sıralanmışlardır. Katılımcılar büyük veri ve algoritmaların avantajları için kişiselleştirme ve doğru hedefleme (%47,8), reklamların hedeflenen müşteriye doğrudan ulaşması ve reklam harcamalarının azalmasına (% 43,5) katkıda bulunmasını, öncelikli olarak işaret etmişlerdir. Buna ek olarak katılımcılar, büyük veri ve algoritmanın, müşterilerin tüm bilgilerine erişebilme yeteneğinin, etik çizgileri aştığını ve bunun bir dezavantaj olduğunu düşündüklerini vurgulamışlardır. Sonuç olarak Türkiye’de dijital reklamcılığın dönüşümünde büyük veri ve algoritma büyük bir öneme sahiptir ve firmalar pazarda etkin olabilmek ve rekabet ortamında kaybolmamak için bu sistemden oldukça sık ve etkili bir şekilde faydalanmaktadırlar.
Dijital reklamcılıkta büyük veri ve algoritmaların kullanımı
Keywords: Büyük Veri; Algoritma; Dijital Reklamcılık; Dijital Medya; Nitel Araştırma; Big Data; Algorithm; Digital Advertising; Digital Media; Qualitative Research